Dissociation between wanting and liking for alcohol and caffeine: A test of the Incentive Sensitisation Theory. (July 2017) - Arulkadacham, Lilani J; Richardson, Ben; Staiger, Petra K; Kambouropoulos, Nicolas; O'Donnell, Renée L; Ling, Mathew
Limited human studies have directly tested the dissociation between wanting and liking with human substance users, a core tenet of the Incentive Sensitisation Theory (IST). The aim of this study is to test the dissociation between wanting and liking in humans across two commonly used licit substances, alcohol and caffeine. The STRAP-R (Sensitivity To Reinforcement of Addictive and other Primary Rewards) questionnaire was administered to 285 alcohol users (mean age=33.30, SD= 8.83) and 134 coffee users (mean age=33.05, SD=8.10) ranging in their levels of substance use to assess wanting and liking. Findings showed that in high risk alcohol users wanting may drive alcohol consumption more so than liking, compared with low risk alcohol users. However, wanting and liking did not significantly dissociate as alcohol consumption increased. These findings partially support IST. Additionally, IST was not supported in coffee users. It is possible that caffeine functions differently at the neurological level compared with alcohol, perhaps explaining the lack of dissociation emerging in coffee users as caffeine use increased. Nevertheless, the current study makes several contributions to IST research. Future studies should focus on utilising the STRAP-R with a clinically dependent sample to test the dissociation between wanting and liking.